2012
DOI: 10.1148/radiol.12120614
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Diagnoses to Suspected Appendicitis at CT

Abstract: In adult patients clinically suspected of having acute appendicitis, abdominopelvic CT frequently identifies an alternative cause for symptoms, which often requires hospitalization and surgery for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 30 publications
1
35
1
Order By: Relevance
“…However, we showed that the probability of achieving a correct alternative diagnosis is lower when scanning the pelvis only rather than the entire abdomen and pelvis. This confirms the major drawback of focused pelvic acquisition is missing alternative diseases by ignoring the upper abdomen [8,14]. In addition, our study shows that the visualisation of the appendix is less frequent with pelvic focused CT than with other acquisitions.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, we showed that the probability of achieving a correct alternative diagnosis is lower when scanning the pelvis only rather than the entire abdomen and pelvis. This confirms the major drawback of focused pelvic acquisition is missing alternative diseases by ignoring the upper abdomen [8,14]. In addition, our study shows that the visualisation of the appendix is less frequent with pelvic focused CT than with other acquisitions.…”
Section: Discussionsupporting
confidence: 83%
“…Dose reduction should, however, be considered in young patients only, and elder patients such as those included in our study sample could need a thorough imaging protocol rather than a radiation saving protocol. Nevertheless, as compared with young adults, patients older than 65 years present more frequently a cause of symptoms other than acute appendicitis and are thus an appropriate model for investigating diseases alternative to acute appendicitis [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 CT is the most accurate imaging technique for evaluating suspected acute appendicitis and alternative etiologies of right lower quadrant pain. 14,15 Drawbacks of CT include the use of ionizing radiation and the nephrotoxic potential of intravenous iodinated contrast agents. Ultrasound does not use ionizing radiation but is operator-dependent and has a significantly lower diagnostic accuracy.…”
Section: Mr Imaging Findings With Computed Tomography Correlation Acumentioning
confidence: 99%
“…[4][5][6][7][8] Thus, the correct -and differential -diagnosis of AA is of great importance in informing the choice of clinical treatment.…”
Section: Introductionmentioning
confidence: 99%